Az ortopédiai nagymǔtétek során alkalmazott terápiás szuggesztiók hatása a beteg gyógyulására - Csenge, Szeverenyi; Zoltan, Csernatony; Agnes, Balogh; Tunde, Simon; Zoltan, Kekecs ; 0000-0001-9247-9781; Katalin, Varga (Orvosi Hetilap, 2018)
Introduction and aim: Hip and knee replacement surgery is very demanding for patients. Medication consumption is further increased by perioperative anxiety. Besides pain killer and anxiolytic medications, patients' recovery can be enhanced by applying therapeutic suggestions, which are easily applicable during the patient-physician communication. Method: In our prospective, randomized, controlled study we examined the effects of positive suggestions on patients undergoing hip or knee arthroplasty in spinal anaesthesia. Members of the suggestion group received the therapeutic suggestions during a pre-surgery physician visit, and by listening to an audio recording during surgery. Results: Compared to the control group (n = 50), in the suggestion group (n = 45) the need of medication (pain killer and adjuvant pain medication) during the surgery was lower (p = 0.037), the mean change from baseline in the well-being of the patients was better on the 2nd [1.31 (0.57; 2.04); p<0.001] and 4th [0.97 (0.23; 1.7); p = 0.011] postoperative day and less transfusion had to be administered (OR: 2.37; p = 0.004). However, there was no difference between the two groups in the postoperative need of medications, in the length of hospitalisation and in the frequency of complications. Conslusion: Our results indicate that the administration of therapeutic suggestions in the perioperative period may be beneficial for orthopaedic surgery patients.
Keywords: Hip replacement; Knee replacement; Pain; Suggestion; Well-being